Maternal thyroid function in women undergoing controlled ovarian hyperstimulation during IVF and its relation to reproductive outcome. - Buvanes C,; Abdul Kadir AK,; Zainul Rashid ZR,; Omar MH,; Natasha Ain MN, (Department of Surgery, UKM Medical Centre, 2014)
A prospective observational study undertaken in 2013 at Medically Assisted Conception unit of UKM Medical Centre. The study was carried out among women scheduled for COH in preparation in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI). A total of 88 were included for final analysis. Serum thyroid levels were measured at 4 points; before stimulation (T1), day 10 –13 of cycle (T2), during oocyte retrieval (T3) and at one week following embryo transfer (T4). Results were analyzed according to reproductive outcome.